(untitled) (Texas Journal of Philology, Culture and History, 2023)
In this article, an opinion is expressed about the phonetic phenomena in the speech of amateurs, the stylistic possibilities that emerge as a result of this phenomenon. The article describes the importance of phonostylistic tools in creating meaning, their methodological aspects related to their use in comic texts.